Biology of exploited groupers (Epinephelidae family) around La Réunion Island (Indian Ocean) - Mahé, Kélig; Gentil, Claire; Brisset, Blandine; Evano, Hugues; Lepetit, Camille; Boymond-Morales, Romane; Telliez, Soléne; Dussuel, Antoine; Rungassamy, Tévamie; Elleboode, Romain; MacKenzie, Kirsteen; Roos, David (Frontiers in Marine Science, 2022)
The groupers (Epinephelidae family) are demersal species that are a vulnerable resource due to increasing fishing pressure around Reunion Island. Five species of groupers are among the main species exploited by commercial and recreational fisheries around La Réunion Island: blacktip grouper (Epinephelus fasciatus; Forsskål 1775), oblique-banded grouper (Epinephelus radiatus; Day 1868), golden hind (Cephalopholis aurantia, Valenciennes 1828), white-edged lyretail (Variola albimarginata; Baissac 1953) and yellow-edged lyretail (Variola louti; Fabricius 1775). From 2014 to 2021, a total of 482 individuals were caught. Body length-weight relationships showed a significant relationship between total length and total weight for all species. Among the five grouper species, significant sexual dimorphism was only observed for E. fasciatus. For each grouper species, the von Bertalanffy model gave the best fit for the ageing data. While the unconstrained von Bertalanffy model fitted very well to the data of four species (C. aurantia, E. radiatus; V. albimarginata and V. louti), the Gompertz model gave the best fit for the ageing data of E. fasciatus. The parameters of these growth models gave the asymptotic length TL∞ (from 28.9 cm for C. aurantia to 76.6 cm for V. louti), and growth rate K (from 0.16 for V. albimarginata to 0.40 for E. fasciatus) for each species. Consequently the growth performance index for these grouper species varied from 2.40 to 3.09. Based on gonad observation, the length at first sexual maturity of females varied between 14 to 18 cm for C. aurantia, E. fasciatus and V. albimarginata, to 32 cm for E. radiatus and 34 cm for V. louti. The corresponding age at first sexual maturity by species ranged from 1.67 to 6.65 years old. Reproduction intensity showed that reproduction peaked for a period of three months each year. Three species (C. aurantia; E. fasciatus and V. louti) reproduced mainly in summer, between December to March, while E. radiatus and V. albimarginata exhibited peak spawning between April and July. The updated biological parameters for these five species are invaluable inputs into the future assessment and management of these important commercial species.